The underground church : nonviolent resistance to the Vatican empire - Kautzer, Kathleen (Studies in critical social sciences, 2012)
Drawing on theories of religious movements and nonviolent resistance strategies, this book analyzes the Reform Movement of liberal American Catholics who for over four decades have sustained a movement to expand on the reforms and visions of Vatican II. In the face of backlash from church officials, reformers have moved in a sectarian direction.